Miniature high dynamic range time-resolved CMOS SPAD image sensors - Al Abbas, Tarek (The University of Edinburgh, 2019)
Since their integration in complementary metal oxide (CMOS) semiconductor technology in 2003, single photon avalanche diodes (SPADs) have inspired a new era of low cost high integration quantum-level image sensors. Their unique feature of discerning single photon detections, their ability to retain temporal information on every collected photon and their amenability to high speed image sensor architectures makes them prime candidates for low light and time-resolved applications. From the biomedical field of fluorescence lifetime imaging microscopy (FLIM) to extreme physical phenomena such as quantum entanglement, all the way to time of flight (ToF) consumer applications such as gesture recognition and more recently automotive light detection and ranging (LIDAR), huge steps in detector and sensor architectures have been made to address the design challenges of pixel sensitivity and functionality trade-off, scalability and handling of large data rates. The goal of this research is to explore the hypothesis that given the state of the art CMOS nodes and fabrication technologies, it is possible to design miniature SPAD image sensors for time-resolved applications with a small pixel pitch while maintaining both sensitivity and built -in functionality. Three key approaches are pursued to that purpose: leveraging the innate area reduction of logic gates and finer design rules of advanced CMOS nodes to balance the pixel’s fill factor and processing capability, smarter pixel designs with configurable functionality and novel system architectures that lift the processing burden off the pixel array and mediate data flow. Two pathfinder SPAD image sensors were designed and fabricated: a 96 × 40 planar front side illuminated (FSI) sensor with 66% fill factor at 8.25μm pixel pitch in an industrialised 40nm process and a 128 × 120 3D-stacked backside illuminated (BSI) sensor with 45% fill factor at 7.83μm pixel pitch. Both designs rely on a digital, configurable, 12-bit ripple counter pixel allowing for time-gated shot noise limited photon counting. The FSI sensor was operated as a quanta image sensor (QIS) achieving an extended dynamic range in excess of 100dB, utilising triple exposure windows and in-pixel data compression which reduces data rates by a factor of 3.75×. The stacked sensor is the first demonstration of a wafer scale SPAD imaging array with a 1-to-1 hybrid bond connection. Characterisation results of the detector and sensor performance are presented. Two other time-resolved 3D-stacked BSI SPAD image sensor architectures are proposed. The first is a fully integrated 5-wire interface system on chip (SoC), with built-in power management and off-focal plane data processing and storage for high dynamic range as well as autonomous video rate operation. Preliminary images and bring-up results of the fabricated 2mm² sensor are shown. The second is a highly configurable design capable of simultaneous multi-bit oversampled imaging and programmable region of interest (ROI) time correlated single photon counting (TCSPC) with on-chip histogram generation. The 6.48μm pitch array has been submitted for fabrication. In-depth design details of both architectures are discussed.
Keywords: SPADs; miniature SPAD image sensors; pixel pitch; SoC; TCSPC